Introduction to Second National Workshop on Nutrition Research Designs And Methods. - Ausman, Lynne. (Tufts University. Tisch Library., 2019)
This presentation was the welcome remark on the second National Workshop on Nutrition Research Designs and Methods.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy